2023
DOI: 10.3389/fnut.2023.1207754
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental methionine selenium effects on egg yolk physicochemical, functional, and protein structure during storage

Abstract: To clarify the effect of the addition of methionine selenium on the physicochemical, functional, and protein structural properties of egg yolk during storage. We analyzed the changes in the main indicators of egg yolks stored at 4°C and 25°C for 28 days. The results showed that the increase in water content and pH, and the decrease in absolute zeta potential and apparent viscosity of the selenium-rich egg yolks (Se-group) during storage were smaller than those of the control group egg yolks (C-group). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…However, dietary supplementation with SS and SEC tended to mitigate the decrease of the yolk index in eggs stored at 25 °C. Consistent with our findings, previous studies demonstrated that Se enrichment increased the yolk index during storage by enhancing the strength of the egg yolk membrane and reducing the transfer of albumen water to the yolk [ 15 , 31 ]. Our results indicated a positive effect of feeding laying hens a diet supplemented with SS or SEC on preserving the yolk quality during storage.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, dietary supplementation with SS and SEC tended to mitigate the decrease of the yolk index in eggs stored at 25 °C. Consistent with our findings, previous studies demonstrated that Se enrichment increased the yolk index during storage by enhancing the strength of the egg yolk membrane and reducing the transfer of albumen water to the yolk [ 15 , 31 ]. Our results indicated a positive effect of feeding laying hens a diet supplemented with SS or SEC on preserving the yolk quality during storage.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary Se supplementation increased GSH-Px, T-SOD, and CAT activity in the serum and livers of hens [45]. Our study showed that SEC, SEY, or SEC + SEY alleviated the decrease in yolk T-AOC level and T-SOD activity in eggs stored at 4 • C and 25 • C. Similar results were obtained by Chen et al [15], who reported that dietary supplementation with Se improved yolk antioxidant status during storage. In the present study, SEC and SEY were rich in organic Se.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations